Justice-Sensitive Poverty Policy Implementation in Rural Indonesia: Administrative, Normative, and Political Constraints in Sikka Regency - Margaretha Movaldes Da Maga Bapa; Aloysius Liliweri; Ajis Salim Adang Djaha; Nursalam Nursalam; Laurensius Petrus Sayrani (Universitas Teuku Umar, 2026)
This study examines why poverty alleviation policies in rural Indonesia may remain administratively operational while producing limited justice-sensitive outcomes for the least advantaged. Rather than claiming that justice is absent from implementation research, the article argues that justice is insufficiently operationalized as a standard for assessing who benefits, who is excluded, and how allocation decisions are made. It develops a justice-sensitive implementation framework that integrates administrative implementation analysis with Rawlsian principles of fair equality of opportunity and the difference principle. Using an interpretive qualitative case study in Sikka Regency, Nusa Tenggara Timur, the research draws on interviews, observation, and document analysis. The findings indicate that limited justice-sensitive implementation emerges through the interaction of fragmented coordination, unreliable poverty data, weak institutional follow-through, targeting errors, uneven procedural accessibility, symbolic participation, patronage, and rural territorial constraints. The study contributes by distinguishing administrative activity from justice-sensitive implementation and by showing how technical weaknesses in data, coordination, and participation can become mechanisms through which distributive and procedural injustice is reproduced. The findings should be interpreted analytically rather than statistically, given the single-case qualitative design.